2018
DOI: 10.1016/j.neuroimage.2018.03.039
|View full text |Cite
|
Sign up to set email alerts
|

Mapping working memory retrieval in space and in time: A combined electroencephalography and electrocorticography approach

Abstract: In this study, we investigated the time course and neural correlates of the retrieval process underlying visual working memory. We made use of a rare dataset in which the same task was recorded using both scalp electroencephalography (EEG) and Electrocorticography (ECoG), respectively. This allowed us to examine with great spatial and temporal detail how the retrieval process works, and in particular how the medial temporal lobe (MTL) is involved. In each trial, participants judged whether a probe face had bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 67 publications
(107 reference statements)
0
21
0
Order By: Relevance
“…Loughnane et al (2016) found initial evidence by looking at condition differences to suggest that stimulus-locked negative peaks around 200 ms (N200) influence the onset of a neural correlate of evidence accumulation. In other studies, single-trial EEG potentials thought to be generative of N200 peaks were suspected to be related to a "pre-attentive" phase before evidence accumulation (Zhang et al, 2016(Zhang et al, , 2018. Interestingly, single-neuron recordings of evidence accumulation from lateral intraparietal areas (LIP) in primates typically begin at similar time periods (≈ 200 ms) after an experimental stimulus is displayed (Roitman and Shadlen, 2002;Shadlen and Kiani, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Loughnane et al (2016) found initial evidence by looking at condition differences to suggest that stimulus-locked negative peaks around 200 ms (N200) influence the onset of a neural correlate of evidence accumulation. In other studies, single-trial EEG potentials thought to be generative of N200 peaks were suspected to be related to a "pre-attentive" phase before evidence accumulation (Zhang et al, 2016(Zhang et al, , 2018. Interestingly, single-neuron recordings of evidence accumulation from lateral intraparietal areas (LIP) in primates typically begin at similar time periods (≈ 200 ms) after an experimental stimulus is displayed (Roitman and Shadlen, 2002;Shadlen and Kiani, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Many cognitive tasks studied by fMRI average less than 2 s and this methodology is not appropriate for these. We have developed complementary HSMM‐MVPA methods with EEG, MEG and ECoG that have shown success in parsing such brief tasks into states (e.g., Anderson, Pyke, & Fincham, ; Anderson, Zhang, et al, ; Anderson et al, 2018; Zhang, Walsh, & Anderson, , Zhang, van Vugt, Borst, & Anderson, ). On the other hand, the current results indicate that one can be fairly optimistic analyzing fMRI data from tasks in the 5 s to 1‐min range, provided one is not trying to identify a great many brief states.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, gamma oscillations G in frontal, temporal, parietal, and occipito-temporal cortices were shown to increase approximately linearly with memory load in implanted epileptic patients performing a delayed match-to-sample task (Howard et al, 2003). In another study, Zhang et al (2018) used ECOG (see iEEG G ) to explore retrieval and maintenance of faces in working memory and found that while activity in the medial temporal lobe reflected active maintenance of the stu-died face set in the decision stage, the frontal cortex guided the decision by means of theta coupling with the medial temporal lobe. Recently, Miller, Lundqvist and Bastos (2018) proposed a revision of the classical model of working memory, suggesting that the top-down control of working memory content arises from the interaction between oscillatory patterns in different frequency bands (i.e., gamma and alpha/beta).…”
Section: Invasive Brain Recordingsmentioning
confidence: 93%
“…Human iEEG G recordings show that theta (Meltzer et al, 2008;Raghavachari et al, 2001Raghavachari et al, , 2006Zhang et al, 2018), alpha (Meltzer et al, 2008) and broadband gamma (Howard et al, 2003;Jensen et al, 2007;Mainy et al, 2007;Meltzer et al, 2008) band oscillations G spanning across frontal, parietal, and sensory cortices are also associated with working memory (See Roux & Uhlhaas, 2014 for a review). Working memory related oscillations G were localized to the frontoparietal networks, however their role seems to be modulatory (e.g.…”
Section: Invasive Brain Recordingsmentioning
confidence: 99%